FORMATION OF PRESENT RESPONSIBILITY IN ELEMENTARY SCHOOL STUDENTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This topic explores the development of present responsibility in elementary school students, focusing on their ability to manage tasks, follow rules, and take ownership of their actions. The annotation will cover the psychological and cognitive aspects of responsibility formation, as well as the role of parents, teachers, and the school environment in fostering a sense of accountability and conscientiousness in young children. Additionally, it will examine the impact of cultivating present responsibility on students' academic performance, social interactions, and long-term behavioral outcomes. The annotation will draw from a range of scholarly sources, including developmental psychology research, educational theories, and empirical studies on child development and character education. It will provide insights into the factors that contribute to the successful cultivation of present responsibility in elementary school students and offer implications for educators, parents, and policymakers in promoting positive character development in young learners.